Constraints Faced by Sugarcane Growers and Future Prospects for Technology Promotion in the Lucknow Division of Uttar Pradesh - Anurag Dixit; N. R. Meena; R.K. Doharey; Yash Pateriya; Arvind Kumar; Amrit Warshini (The Bioscan, 2025)
Sugarcane is a vital cash crop in Uttar Pradesh, contributing significantly to the livelihoods of rural farmers and the regional economy. However, despite advancements in production technologies, their adoption remains limited among growers. This study was conducted to identify the major constraints faced by sugarcane farmers in adopting improved production technologies and to explore the future prospects for technology promotion in the Lucknow Division. Primary data were collected from 320 respondents across two districts—Lakhimpur Kheri and Lucknow—using a pre-tested interview schedule. The analysis was carried out using the Mean Percentage Score (MPS) to rank constraints and assess the level of agreement on potential future interventions. The findings of the study highlighted several key constraints affecting sugarcane technology adoption. The most prominent issues included a lack of interaction with extension agents and progressive farmers or agricultural universities (Mean Percent Score [MPS] = 90.00), limited motivation and awareness regarding modern agricultural practices (MPS = 85.00), and the absence of effective leadership among progressive farmers to guide others (MPS = 74.92). Additionally, low profitability due to inadequate Fair and Remunerative Price (MPS = 86.25) and a shortage of labour during critical farming operations (MPS = 84.22) were also significant barriers. District-specific challenges were also observed. In Lakhimpur Kheri, the high cost of both manual and mechanized harvesting was reported as a major constraint (MPS = 88.59). Conversely, in Lucknow, the lack of nearby sugar mills or local crushers emerged as a primary concern (MPS = 88.13). With regard to future prospects, respondents strongly supported the revision of FRP policies (MPS = 95.47) and the establishment of local sugarcane processing units in Lucknow (MPS = 99.06) as critical interventions. The study concludes that enhancing the adoption of sugarcane production technology in the region requires a multifaceted approach. This should include policy-level reforms, the strengthening of extension services, and the development of localized value chains to ensure sustainable and inclusive agricultural growth.